Iklan Media Sosial dan Pengaruhnya Terhadap Niat Beli Konsumen - Patrina, Amelia (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
The rapid increase in social media users has given rise to a new form of advertising for businesses called social media advertising. Advertisers have long faced one of the most significant challenges: low consumer acceptance of ads. It is important to identify the most prominent elements of social media ads that influence how consumers perceive them. The aim of this research is to find out the factors that affect perceptions of social media advertising and its influence on customers' purchase intentions. This study uses a quantitative approach with a survey method. The target population for this survey is social media users. Structural Equation Modeling is used to evaluate the constructs. A questionnaire was prepared and distributed to approximately 175 respondents via Google Forms. 175 responses were used for the pilot study. The questionnaire consists of 26 indicators. This study uses SEM PLS for data analysis. The results of the data analysis show that elements such as attention-grabbing details and emotional appeal have a significant impact on customers' purchase intentions. Sufficient emphasis on the characteristics mentioned above will help in the development of effective social media marketing and enhance consumer purchase intentions.